Research on asset-based community development - Qiaoyu, Ma; Rosnon, Mohd Roslan; Amin, Samir Muhazzab; Sufian Burhan, Nik Ahmad (Human Resource Management Academic Research Society, 2024)
Asset-based community development is a development method based on the internal resources and capabilities of the community, which aims to promote the development of the community and improve the quality of life of community residents by mobilizing and integrating these assets. This paper examines the principles, practice, and promise of asset based community development. First, the theoretical basis of asset-based community development is expounded, including asset theory, social capital theory and community capacity theory. Then, it introduces the practical methods of asset-based community development, including community asset identification and assessment, community mobilization and integration, asset-oriented planning and policy, etc. Finally, prospects for asset-based community development are discussed, including challenges and opportunities for sustainable development, community engagement, and community innovation.